Extracellular MicroRNA-92a Mediates Endothelial Cell–Macrophage Communication. Issue 12 (December 2019) - Chang, Ya-Ju; Li, Yi-Shuan; Wu, Chia-Ching; Wang, Kuei-Chun; Huang, Tzu-Chieh; Chen, Zhen; Chien, Shu
Abstract : Objective: Understanding message delivery among vascular cells is essential for deciphering the intercellular communications in cardiovascular diseases. MicroRNA (miR)-92a is enriched in endothelial cells (ECs) and circulation under atheroprone conditions. Macrophages are the primary immune cells in atherosclerotic lesions that modulate lesion development. Therefore, we hypothesize that, in response to atheroprone stimuli, ECs export miR-92a to macrophages to regulate their functions and enhance atherosclerotic progression. Approach and Results: We investigated the macrophage functions that are regulated by EC miR-92a under atheroprone microenvironments. We first determined the distributions of functional extracellular miR-92a by fractionating the intravesicular and extravesicular compartments from endothelial conditioned media and mice serum. The results indicate that extracellular vesicles are the primary vehicles for EC miR-92a transportation. Overexpression of miR-92a in ECs enhanced the proinflammatory responses and low-density lipoprotein uptake, while impaired the migration, of cocultured macrophage. Opposite effects were found in macrophages cocultured with ECs with miR-92a knockdown. Further analyses demonstrated that intravesicular miR-92a suppressed the expression of target gene KLF4 (Krüppel-like factor 4) in macrophages, suggesting a mechanism by which intravesicular miR-92a regulates recipient cell functions. Indeed, the overexpression of KLF4 rescued the EC miR-92a–induced macrophage atheroprone phenotypes. Furthermore, an inverse correlation of intravesicular miR-92a in blood serum and KLF4 expression in lesions was observed in atherosclerotic animals, indicating the potential function of extracellular miR-92a in regulating vascular diseases. Conclusions: EC miR-92a can be transported to macrophages through extracellular vesicles to regulate KLF4 levels, thus leading to the atheroprone phenotypes of macrophage and, hence, atherosclerotic lesion formation. Abstract : Supplemental Digital Content is available in the text.